Perancangan Sistem Informasi Persediaan dan Penjualan Pada PT. Anzon Autoplaza Pontianak Dengan Pencarian Sekuensial - Sugito Sudjalmo; Thommy Willay (Institut Bisnis Nusantara, 2025)
PT. Anzon Autoplaza is the official dealer of Toyota vehicle sales in Pontianak. Currently, the inventory and sales system in the sales department is still using a manual system. The company staff is having difficulty controlling and monitoring the inventory of vehicles for sale. Researchers designed an inventory and sales information system using Microsoft Visual Studio 2015 (.NET) with the aim of providing a solution to expedite and enhance the accuracy of vehicle inventory information during sales transactions. In this study, the researcher used a descriptive research method and data collection through interviews, observations, and literature review. The data search method using sequential search techniques. System analysis techniques are object-oriented, while the modeling tool used is the Unified Modeling Language. (UML). As a result, the researchers developed an information system at PT. Anzon Autoplaza that can enhance efficiency and accuracy in processing inventory and sales data. It is hoped that there will be an improvement in the quality of services to the company's consumers, as well as an increase in the effectiveness and efficiency of work